DETERMINATION OF DIVIDEND POLICY OF MANUFACTURING COMPANIES IN INDONESIA - Husaini, Husaini; Marzuki, Marzuki; Nurhasanah, Nurhasanah (CV. Radja Publika, 2021)
This study examines the factors that determine (determination) dividend policy in manufacturing companies in Indonesia. In general, economic conditions in Indonesia are still in the emerging market category. As a developing country, Indonesia's capital market is relatively large and has its own characteristics which are reflected in investor behavior and government regulations in the capital market. Indonesia, in its behavior in the capital market adheres to a civil law system, meaning that investors are given the widest freedom to conduct transactions in the capital market, especially in the wrong amount owned by investors. The variables used to analyze dividend policy are profitability, free cash flows, firm size and leverage. This study only focuses on manufacturing companies that distribute dividends with an observation period from 2015-2019. The sampling method used purposive sampling and obtained 145 companies that distribute dividends. The data was processed using panel data regression analysis with analysis tools using E-Views software. From the research, it is found that the ROA and F_SIZE variables have a positive and significant effect on the DPR. FCF and Leverage variables measured by (TDTE) have a negative and significant effect on dividend policy as measured by the DPR in manufacturing companies in Indonesia.